2020
DOI: 10.3389/fphar.2020.549057
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Attenuates Acetaminophen-Induced Hepatotoxicity by Activating AMP-Activated Protein Kinase/Carnitine Palmitoyltransferase I Pathway

Abstract: Overuse of acetaminophen (APAP) is a major cause of drug-induced liver failure at the clinics. Apigenin (API) is a natural flavonoid derived from Matricaria chamomilla. The aim of the present study was to investigate the amelioration function of API in APAP-induced hepatotoxicity both in vitro and in vivo and investigate its potential mechanisms. Analysis results of the activities of serum alanine and aspartate aminotransferases (ALT and AST), malondialdehyde, myeloperoxidase (MPO), and reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Together, our results confirmed that apigenin activated autophagy and regulated the TFEB level through the AMPK/mTOR signaling pathway. It is worth noting that the effect of apigenin on AMPK/mTOR signaling is consistent with previously reported studies (Lu et al, 2019;Zhang et al, 2020a).…”
Section: Discussionsupporting
confidence: 92%
“…Together, our results confirmed that apigenin activated autophagy and regulated the TFEB level through the AMPK/mTOR signaling pathway. It is worth noting that the effect of apigenin on AMPK/mTOR signaling is consistent with previously reported studies (Lu et al, 2019;Zhang et al, 2020a).…”
Section: Discussionsupporting
confidence: 92%
“…Molecular docking is a computer simulation algorithm for small molecules and proteins to recognize each other through geometric accouplement and energy matching [ 53 ]. Among the multitudinous docking analysis indicators, the binding energy is an important index for evaluating the stability of the results of docking.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a laminectomy was performed at the T9-T10 level and moderate contusion injury was made by dropping an impactor (2 mm diameter, 12.5 g, 2 cm in height) onto the surface of the spinal cord. Two hours after surgery, mice were treated with zinc gluconate (30 mg/kg, intraperitoneally) with and without compound C (10 mg/kg, intraperitoneally) [ 23 ]. Postoperative care was given, and the mice were given the drug daily until the third day.…”
Section: Methodsmentioning
confidence: 99%